Cooperative Learning Strategy to Improve Student Learning Outcomes on the Theme of Always Saving Energy at MI Nurul Ihsan - Haryati (DEEP LEARNING: Journal of Educational Research, 2025)
This study investigates the effectiveness of domino card media in improving science learning outcomes for students at MIS Mawu. Recognizing the limitations of traditional, passive learning methods in fostering deep understanding and engagement in science, this research explores the potential of an interactive and collaborative learning tool. Domino cards, designed to connect various scientific concepts, terms, or processes, were implemented as a pedagogical intervention. The study examines the impact of this medium on student engagement, collaborative learning skills, critical thinking abilities, and ultimately, their academic achievement in Ilmu Pengetahuan Alam (Natural Science). Data was collected through [mention data collection methods if specified in a full paper, e.g., pre- and post-tests, observations, student feedback]. The findings of this research aim to provide empirical evidence on the efficacy of domino card media as a tool for enhancing science education in the specific context of MIS Mawu. The results of this study [mention key findings if specified in a full paper, e.g., demonstrated a statistically significant improvement in student test scores, increased student engagement during lessons, enhanced collaborative problem-solving skills]. These findings suggest that the application of domino card media offers a valuable and engaging approach to teaching science, promoting active learning, collaboration, and critical thinking among students at MIS Mawu. The interactive and visual nature of the domino cards facilitated a deeper understanding of interconnected scientific concepts and catered to diverse learning styles. This research contributes to the growing body of literature on innovative teaching methodologies in science education and provides practical insights for educators seeking to enhance student learning outcomes through the use of engaging and hands-on media.